Facial expression at retrieval affects recognition of facial identity - Chen, Wenfeng; Liu, Chang Hong; Li, Huiyun; Tong, Ke; Ren, Naixin; Fu, Xiaolan (Frontiers in Psychology, 2015)
It is well known that memory can be modulated by emotional stimuli at the time of encoding and consolidation. For example, happy faces create better identity recognition than faces with certain other expressions. However, the influence of facial expression at the time of retrieval remains unknown in the literature. To separate the potential influence of expression at retrieval from its effects at earlier stages, we had participants learn neutral faces but manipulated facial expression at the time of memory retrieval in a standard old/new recognition task. The results showed a clear effect of facial expression, where happy test faces were identified more successfully than angry test faces. This effect is unlikely due to greater image similarity between the neutral learning face and the happy test face, because image analysis showed that the happy test faces are in fact less similar to the neutral learning faces relative to the angry test faces. In the second experiment, we investigated whether this emotional effect is influenced by the expression at the time of learning. We employed angry or happy faces as learning stimuli, and angry, happy, and neutral faces as test stimuli. The results showed that the emotional effect at retrieval is robust across different encoding conditions with happy or angry expressions. These findings indicate that emotional expressions affect the retrieval process in identity recognition, and identity recognition does not rely on emotional association between learning and test faces.